Environment-friendly bulk Fe16N2 permanent magnet: Review and prospective - Wang, Jian-Ping (Journal of magnetism and magnetic materials, 2020)
•α″-Fe16N2 was viewed as a mystery material because of inconclusive arguments in 1990s, including many controversial reports at two specific symposia at MMM conferences.•Then the topic was largely dropped by the magnetic research community.•The key controversies around this material have been successfully addressed through our long and persistent effort from 2002 to 2012, which was reported at APS Marching Meeting 2010 and INTERMAG 2012.•Since then, α″-Fe16N2 has been picked up as one of the most promising rare-earth-free magnet candidates because of its usage of environment-friendly raw materials, its confirmed giant saturation magnetization and reasonably high magnetic anisotropy constant.•Iron nitride magnet is of great interest as a magnetic material for the applications at relatively low temperature (<150 °C) ranging from speaker magnets, magnets in hard disk drives and all kinds of electrical motors, wind turbines, and other power generation machines.•A perspective review on the synthesis of bulk α″-Fe16N2 compound permanent magnet in past was presented here on the aspects of material processing and magnetic characterizations.•Specifically, we introduce and discuss our efforts to prepare the bulk Fe16N2 compound permanent magnet by using four different approaches, including an ion implantation method, a nanoparticle based approach, a high-temperature nitridation method based on foils, wires and melt-spun ribbons and a low-temperature nitridation method based on foils and ribbons.•With our recent progress and many good on-going activities by researchers worldwide, we believe that α″-Fe16N2 compound permanent magnet is in an accelerating stage to be an alternative environment-friendly magnet candidate. α″-Fe16N2 had been viewed as a mystery material because of inconclusive arguments in the 1990s, including many controversial reports at two MMM conference symposia, and the topic was then largely dropped by the magnetic research community. The key controversies around this material have now been successfully addressed through our long and persistent efforts from 2002 to 2012, first reported in APS 2010 and then at INTERMAG 2012. Since then, α″-Fe16N2 has been picked up as one of the most promising rare-earth-free magnet candidates because of its use of environment-friendly raw materials, confirmed giant saturation magnetic flux density (2.9 T), and reasonably high magnetic anisotropy constant (1.8 MJ/m3). Its coercivity temperature coefficient (~0.4 Oe/°C) in the range of 27–152 °C is two orders of magnitude lower than that of commercial NdFeB magnets (e.g. N40 ~ −81.9 Oe/K). The iron nitride magnet is of great interest as a magnetic material for applications working at relatively low temperature (<150 °C) and not requesting high coercivity. These applications range from speaker magnets to magnets in hard disk drives, electrical motors, wind turbines, smart phones, audio devices, and other power generation machines. A perspective review on the synthesis of the bulk α″-Fe16N2 compound permanent magnet is presented here on the aspects of material processing and magnetic characterizations. Specifically, we introduce and discuss our efforts to prepare the bulk Fe16N2 compound permanent magnet by using four different approaches, including an ion implantation method, a nanoparticle based approach, a high-temperature nitridation method based on foils, wires, and melt-spun ribbons, and a low-temperature nitridation method based on foils and ribbons. With our recent progress and many on-going activities by researchers worldwide, we believe that the α″-Fe16N2 compound permanent magnet is in an accelerating stage to be an alternative environment-friendly magnet candidate.